Changes in Inventories in the National Accounts - Fassler, Segismundo (IMF Working Papers; Working Paper ;, 2003)
The principles underlying the recording of changes in inventories are explained in the System of National Accounts, 1993 (1993 SNA), but operational guidelines on their measurement are lacking. This paper elaborates specific statistical techniques and their underlying assumptions for calculating changes in inventories and holding gains when only data on stocks of inventories are available. Several data situations are considered. The authors propose methods for measuring changes in inventories that meet the 1993 SNA principles. The paper also explores possibilities for implementing the proposed improvements and explains the interpretation of data on changes in inventories.